Influence of economics, psychological, sociological and consumers' indebtedness on consumers' propensity to over-indebtedness in Malaysia - Selvajara, Monica (2021)
Debt is a double edge sword; it can create a positive or negative impact on an individuals’ life. However, excessive debt accumulation behaviour of an individual creates a significant unfavourable impact on an individuals’ lives. One of which is, it affects an individuals’ ability to save for a rainy day. Literature states an individuals’ external factors (i.e. economic factor) and internal factors (i.e. psychological factors, sociological, consumers’ indebtedness) affects their tendency to engage in higher debt consumption decision-making (i.e. propensity to over-indebtedness). Although, numerous past researchers had independently viewed the influence of various factors that leads to over-indebtedness; however, these factors are found to vary regionally. This is due to the’ non-observance of the earlier mentioned antecedence in a model and has been suggested in the past research. This study aims to develop a theoretical understanding of an individuals’ behaviour leading towards their propensity to be overindebted in Malaysia. Moreover, the rise in the personal debt issues in Malaysia, created various issues, such as personal insolvency mainly among young working adults. This thesis contributes by analysing the influence of economic, psychological, sociological and consumers’ indebtedness on the propensity to be over-indebted in the local, regional context (i.e. Malaysia). Additionally, the role of consumers’ indebtedness as a mediator between the earlier mentioned exogenous variables and the endogenous variable is determined. In this context, consumers’ indebtedness is a consumers’ obligation towards debt repayment, and the propensity to over-indebtedness is an individuals’ likelihood of debt engagement which is beyond their capacity is subjectively measured. Based on the review of the literature on debt consumption decision-making, three main theories were utilized in this study as follows. Firstly, the Life-Cycle Permanent Income Theory of Consumption [LC-PI]; secondly, Behavioural Economic Theory [BET]; thirdly, Theory of Indebtedness [TI]. To elaborate, LC-PI views the influence of economic factor, BET views the influence of psychological and sociological factor, and TI views the influence of consumer’s indebtedness towards propensity to overindebtedness. Primarily the past researches as studied the influence of economic factor (objectively measured), psychological and sociological factors (subjectively measured) towards the tendency to be overly-indebted in separate studies. However, this research would combine the earlier mentioned exogenous variables to study its direct influence towards propensity to over-indebtedness, along with the mediator variable (i.e. consumers’ indebtedness) in the local research context (i.e. Malaysia). The questionnaire-based survey is used to solicit responses from Malaysian working-adults, identified to be engaged in debt through the usage of filter questions. Data is collected from 247 respondents and were analysed using statistical procedures of SMART PLS version 3.0. The result of partial least square regression model revealed nine out of thirteen exogenous variables to be significant predictors of individuals’ propensity to over-indebtedness (i.e. income shock, consumption shock, risk perception, overconfidence, attitude towards money, materialistic, money management, the culture of debt and consumers’ indebtedness). On the other hand, findings suggested, emotion, myopia, financial literacy and compulsive consumption are found to be insignificant in influencing an individuals’ propensity to be overly-indebted. Additionally, the study presents the test for twelve mediating hypotheses: seven were accepted, and five were rejected. To elaborate, consumers’ indebtedness mediates between income shock, emotion, overconfidence, financial literacy, compulsive consumption, materialistic, money management and propensity to over-indebtedness. Past studies suggest, increase in consumers’ indebtedness can lead a consumer to be over-indebted mainly due to irresponsible lending practice, thus, the higher a consumers’ obligations to repay debt, the higher the propensity to be over-indebted. Thus, a good understanding of consumers’ indebtedness is crucial, since early signs of people getting into financial difficulties are vital for developing intervention policies. Several implications emerged from these empirical findings. This study found that the adverse event of income shock (i.e., job loss, illness, and divorce) can lead an individual into a higher propensity to be over-indebted. Similarly, consumption shock (i.e., engagement into high unsecured financing) are found to lead individuals into a higher propensity to be over-indebted. Moving on, under the psychological factors only risk perception, overconfidence, attitude towards money are found to lead an individual into a propensity to be over-indebted directly. Next, for sociological factors, this study found materialistic, money management, and culture of debt found to lead an individual into a propensity to be over-indebted. This study also found the higher consumers’ indebtedness (i.e., higher obligation to debt repayment) found to fully mediated the relationship between emotion, financial literacy, compulsive consumption and propensity to be over-indebted. This shows, for example, an individual with high perceived financial knowledge are found to be insignificantly engaged in the propensity to be over-indebted. However, with the presence of higher perceived obligation to debt repayment, such individuals are then perceived to be overly-indebted. Therefore, the information provided by this thesis would be useful to both government and its associates to help create awareness on the importance of both external (economic factor), internal (psychological and sociological factor) and influence of consumers’ indebtedness on their propensity to be overly-indebted.